REVOLUSI AKUNTANSI MODERN DENGAN ARTIFICIAL INTELLIGENCE - Agustin Ekadjaja; Maria Bernadet Pek; Florence Delvina (Jurnal Serina Abdimas, 2025)
This Community Service Activity (PKM) is one of the implementations of the Tri Dharma of Higher Education, especially in making a real contribution to society. This program is intended for high school students and students. The implementation of the activity was carried out through face-to-face direct training. The activity began with an initial meeting this was to identify the needs of the school in order to establish cooperation. The theme raised in this activity was "Modern Accounting Revolution with Artificial Intelligence (AI)", which was aimed at high school students and teachers. In this learning activities, participants will be introduced to the understanding and roles of AI in the field of accounting, including how this technology can automate routine work such as data entry and report creation. Thus, accountants will be more focus on data analysis and strategic decision-making. AI also contributes to improving operational efficiency and reducing costs through real-time data processing and error detection capabilities. While AI does not completely replace the role of accountants, it expands the scope of their role as strategic advisors. Challenges such as budget constraints and lack of technological skills still need to be addressed. With this understanding, It is expected that students will be better prepared to face the dynamics of modern accounting and be able to utilize AI-based solutions. The results of this activity are in the form of scientific articles for the publication and registration of Intellectual Property Rights (IPR). As a final stage, a report on the implementation of this PKM activity will be prepared which will be submitted as a form of accountability to DPPM Untar. Kegiatan Pengabdian kepada Masyarakat (PKM) ini adalah suatu bentuk implementasi dari Tri Dharma Perguruan Tinggi, khususnya memberikan kontribusi nyata kepada masyarakat. Program ini dilaksanakan bagi siswa-siswi tingkat SMA. Pelaksanaan kegiatan dilakukan melalui pelatihan langsung secara tatap muka. Kegiatan dimulai dengan pertemuan awal untuk mengidentifikasi kebutuhan pihak sekolah dalam rangka menjalin kerja sama. Tema yang diangkat dalam kegiatan ini adalah "Revolusi Akuntansi Modern dengan Artificial Intelligence (AI)", yang ditujukan kepada siswa-siswi serta para guru SMA. Dalam pelatihan ini, peserta akan diperkenalkan pada konsep dan peran AI dalam bidang akuntansi, termasuk bagaimana teknologi ini dapat mengotomatisasi pekerjaan rutin seperti entri data dan pembuatan laporan. AI juga berkontribusi dalam meningkatkan efisiensi operasional melalui pemrosesan data secara real-time dan kemampuan mendeteksi kesalahan. Meskipun AI tidak menggantikan peran akuntan sepenuhnya, teknologi ini memperluas cakupan peran mereka sebagai penasihat. Tantangan seperti keterbatasan anggaran dan kurangnya keterampilan teknologi masih perlu diatasi. Dengan pemahaman ini, diharapkan para siswa lebih siap dalam menghadapi dinamika akuntansi modern dan mampu memanfaatkan solusi berbasis AI. Hasil dari kegiatan ini berupa artikel ilmiah untuk publikasi dan pendaftaran Hak Kekayaan Intelektual (HKI). Sebagai tahap akhir, akan disusun laporan pelaksanaan kegiatan PKM ini yang akan diserahkan sebagai bentuk pertanggungjawaban kepada DPPM Untar.